2019
DOI: 10.1002/pros.23781
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the CXCL12/CXCR4 axis prevents periurethral collagen accumulation and lower urinary tract dysfunction in vivo

Abstract: Background Several studies show that prostatic fibrosis is associated with male lower urinary tract dysfunction (LUTD). Development of fibrosis is typically attributed to signaling through the transforming growth factor β (TGF‐β) pathway, but our laboratory has demonstrated that in vitro treatment of human prostatic fibroblasts with the C‐X‐C motif chemokine ligand 12 (CXCL12) chemokine stimulates myofibroblast phenoconversion and that CXCL12 has the capacity to activate profibrotic pathways in these cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…In human prostate, an increase in collagen deposition and fibrosis has been identified as a contributing factor of urinary dysfunction [31]. In the mouse, previous studies have shown a significant increase in fibrosis and collagen deposition within the prostatic urethra in mice experiencing LUTD, suggesting that collagen changes can alter normal urination [17,32,33]. We calculated collagen deposition at the midpoint of the prostatic urethra and in the prostate lobes by quantifying birefringence of picrosirius red (PSR) staining under circular polarized light.…”
Section: Resultsmentioning
confidence: 99%
“…In human prostate, an increase in collagen deposition and fibrosis has been identified as a contributing factor of urinary dysfunction [31]. In the mouse, previous studies have shown a significant increase in fibrosis and collagen deposition within the prostatic urethra in mice experiencing LUTD, suggesting that collagen changes can alter normal urination [17,32,33]. We calculated collagen deposition at the midpoint of the prostatic urethra and in the prostate lobes by quantifying birefringence of picrosirius red (PSR) staining under circular polarized light.…”
Section: Resultsmentioning
confidence: 99%
“…15 The use of CXCR4 inhibitors can improve voiding dysfunction caused by bladder inflammation and obesity. 15,32 CXCR4 is an important modulator of nociception and pain sensitivity beyond its involvement in inflammation. Studies on rodents have shown that CXCR4 is expressed in DRG and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The use of CXCR4 inhibitors can improve voiding dysfunction caused by bladder inflammation and obesity. 15 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies using recombinant CXCL12 injections have shown positive effects on tissue regeneration [ 125 , 126 ]. However, there are published studies that seem to contradict these results and dispute the beneficial effects of CXCL12 on urological tissues [ 127 , 128 ]. Nevertheless, these studies focused on the secretion of physiologic CXCL12 that Ray et al showed to form dimers in physiologic conditions.…”
Section: The Regenerative Approachmentioning
confidence: 99%